Risk Analysis and Occupational Safety Control Strategies at Each Workstation in the Production Division of PT XYZ - Widyatama Pratama; Iriani (Yayasan Kita Menulis, 2026)
In facing increasingly intense business competition, companies are required to have human resources with optimal performance in order to achieve organizational goals. Employee performance is influenced by various factors, including work discipline and the implementation of Occupational Safety and Health (OSH). Work discipline reflects employees’ compliance with company rules and procedures, while the implementation of OSH plays an important role in creating a safe, healthy, and comfortable working environment, thereby increasing productivity and reducing the risk of workplace accidents. PT XYZ, a manufacturing company engaged in fertilizer production, has implemented OSH programs in accordance with applicable Indonesian regulations, including Law Number 1 of 1970 concerning Occupational Safety and Government Regulation Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System. Effective OSH implementation is carried out through hazard identification and risk assessment to minimize the potential for occupational accidents and work-related diseases. Through practical work activities, students are given the opportunity to apply academic knowledge directly in an industrial environment and to understand work processes, safety culture, and professional work ethics. The synergy between higher education institutions and the industrial sector is expected to create a productive, safe, and sustainable working environment, while also preparing graduates to face the challenges of the professional world.